2013
DOI: 10.1371/journal.pone.0069221
|View full text |Cite
|
Sign up to set email alerts
|

A Nubian Complex Site from Central Arabia: Implications for Levallois Taxonomy and Human Dispersals during the Upper Pleistocene

Abstract: Archaeological survey undertaken in central Saudi Arabia has revealed 29 surface sites attributed to the Arabian Middle Paleolithic based on the presence of Levallois blank production methods. Technological analyses on cores retrieved from Al-Kharj 22 have revealed specific reduction modalities used to produce flakes with predetermined shapes. The identified modalities, which are anchored within the greater Levallois concept of core convexity preparation and exploitation, correspond with those utilized during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 58 publications
2
54
1
2
Order By: Relevance
“…Within this arid region movements of hunter-gatherer groups across the landscape were most likely facilitated by climatic wet phases. In central Arabia these wet phases are documented in fluvial-lacustrine archives (Breeze et al 2016;Crassard et al 2013;Rosenberg et al 2011;. Negev Humid periods (NHP) are recorded in speleothems (Vaks et al 2006;.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within this arid region movements of hunter-gatherer groups across the landscape were most likely facilitated by climatic wet phases. In central Arabia these wet phases are documented in fluvial-lacustrine archives (Breeze et al 2016;Crassard et al 2013;Rosenberg et al 2011;. Negev Humid periods (NHP) are recorded in speleothems (Vaks et al 2006;.…”
Section: Discussionmentioning
confidence: 99%
“…The Nubian technology is a specific variant of the Levallois technology (GoderGoldberger et al 2016, Guichard & Guichard 19651968;Usik et al 2013;Van Peer 1992) found within Middle Paleolithic techno-complexes at surface sites across the western High Desert in Egypt (Chiotti et al 2009;Olszewski et al 2005), the central Negev highlands (Goder-Goldberger et al 2016) and Arabia (Crassard & Hilbert 2013;Hilbert et al 2016;Rose et al 2011;Usik et al 2013). Common to these finds is a technological package composed of the Levallois Nubian technology alongside both Levallois centripetal and bidirectional modes of production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В материалах вышележащего слоя Е были выде-лены три фации, или три индустриальных комплекса: 1) ябрудийский, ориентированный в основном на по-лучение отщепов и изготовление скребел типа кина; 2) ашельский, связанный с изготовлением преимуще-ственно бифасов, скребел и отщепов; 3) амудийский, предназначенный для изготовления пластин и орудий верхнепалеолитического типа [Copeland, 2000]. В на-чале 1980-х гг.…”
Section: археологический аспектunclassified
“…Обнаруженная в районе палеоозера Джаббах в Аравии индустрия с радиальной системой первич-ного расщепления технологически близка к средне-палеолитической индустрии Леванта типа Табун С, а короткие с широким фасетированным основанием леваллуазские острия, сколотые с однонаправлен-ных конвергентных рабочих поверхностей нуклеусов в Джебель Катефех 1, близки к технологически левал-луазским остроконечникам типа Табун В [Crassard, Hilbert, 2013]. Д. Роуз и Э. Маркс объясняют это либо культурной диффузией, либо вторжением левантий-ских мустьерских (неандертальских.…”
Section: антропологический аспектunclassified